Two new species of the genus Odochilus Harold, 1877 (Coleoptera: Scarabaeidae: Aphodiinae: Odochilini) - Rakovič, Miloslav; Anichtchenko, Alexander (Zootaxa, 2021)
Two new species of the genus Odochilus Harold, 1877 (Coleoptera: Scarabaeidae: Aphodiinae: Odochilini) from the Oriental Region are described as follows: O. shavrini Rakovič & Anichtchenko, new species from the Philippines (Mindanao) and O. borneensis Rakovič & Anichtchenko, new species from Malaysia (Sarawak). Photographs of their habitus are presented. Differential diagnoses are mentioned.